Physical and chemical processes of structure formation of light-weight plugging mortar - Terlyha, Volodymyr; Kovalchuk, Marjana (Видавництво Львівської політехніки, 2013)
Investigations of the processes of structure formation by means of X-ray diffraction, electronic microscopy and differencially-thermal analysis are implemented. The influence of active mineral additives of metakaolin and zeolite on the properties of the plugging mortar and their interaction with the portlancement minerals are established.
Keywords: borehole; oil-well cement; mineral additives; abnormally low stratum pressure; X-ray analysis; microphotographs